Betulinic acid derivatives: a new class of α-glucosidase inhibitors and LPS-stimulated nitric oxide production inhibition on mouse macrophage RAW 264.7 cells. Issue 18 (17th September 2019) - Gundoju, Narayanarao; Bokam, Ramesh; Yalavarthi, Nageswara Rao; Azad, Rajaram; Ponnapalli, Mangala Gowri
Abstract: Chemical manipulation studies were conducted on betulinic acid (1 ), twenty-one new rationally designed analogues of 1 with modifications at C-28 were synthesized for their evaluation of inhibitory effects on α-glucosidase and LPS-stimulated nitric oxide production in mouse macrophage RAW 264.7 cells. Compound2 (IC50 = 5.4 μM) exhibited an almost 1.4-fold increase in α-glucosidase inhibitory activity on yeast α-glucosidase while analogues5 (IC50 16.4 μM) and11 (IC50 16.6 μM) exhibited a 2-fold enhanced inhibitory activity on NO-production than betulinic acid. Abstract :